Guide to Scientific Computing in C++ - Pitt-Francis, Joe; Whiteley, Jonathan (Springer, 2017)
The principle changes in this updated edition are additional material on software testing and on some of the new features introduced in the C++11 standard. When introducing this additional material, we have followed the same philosophy as when writing the first edition of this book. That is, we focus on a concise discussion of the key features that are most useful to the novice and intermediate programmer in the field of scientific computing. We have found this an effective approach when teaching this course to graduate students—once the basics have been mastered, students then have the confidence to find out about less well-used features themselves when they are needed. This second edition would not be as complete—or as enjoyable to update— without discussions with colleagues and other readers of the first edition, including those previously unknown to us who were kind enough to provide constructive feedback. We would like to express our gratitude to all who contributed in this way or offered their encouragement, and to the staff at Springer for inviting us to update the first edition. Finally, we would both again like to thank our families for their love and support.